Purification, Structural Characteristics, and Biological Activities of Exopolysaccharide Isolated From Leuconostoc mesenteroides SN-8 - Wu, Junrui; Yan, Danli; Liu, Yumeng; Luo, Xue; Li, Yang; Cao, Chengxu; Li, Mo; Han, Qi; Wang, Cong; Wu, Rina; Zhang, Lanwei (Frontiers in Microbiology, 2021)
In this study, a novel exopolysaccharide (EPS) was extracted from Leuconostoc mesenteros SN-8 which can be obtained from Da-jiang. After the purification step, EPS-8-2 was obtained with molecular weights of 1.46×105 Da. The structural characterization of EPS indicated that the EPS belonged to the class polysaccharide, mainly composed of glucan and also contained certain mannose residues that were found to be connected by α-1,6 glycosidic bonds. Moreover, the results demonstrated that EPS displayed a significant capacity to scavenge free radical to some extent, and this anti-oxidant potential was found to be concentration dependent. The results further revealed that EPS displayed a significant inhibitory effect on the growth of HepG2 cells by promoting apoptosis and also induced cell cycle arrest in G1 and G2 phases. Overall, these results suggested that EPS can be explored as a possible anti-cancer agent.